Perceptions and practice of health care workers regarding hepatitis B vaccination, Bouaké, Côte d'Ivoire, 2016 - Damus Kouassi; Odile Angbo-Effi; Lepri Aka; M'Bégnan Coulibaly; Sory Soumahoro; Gnissan Yao; Nagho Soro (AOSIS, 2017)
Barriers to immunization are seen in both the general population and the health care workforce. We conducted this study to determine the perception of health workers on vaccination and the immunization of their patients. This cross-sectional descriptive analytical study was carried out among the medical staff in Bouaké, from 10 January to 07 March 2016. The data collected from the interviews were analyzed using Epi info 2000 software and SPSS 17.0. The Chi-2 test and logistic regression were performed and the significance threshold of the tests was 5%. The vaccination status of the 291 health care workers (HCWs) for the hepatitis B virus (HBV) was statistically related to their participation in the course in vaccination during their training (ORa = 1.69, 95% CI: 1.04-2.75 P<0.05) and the systematic verification of the vaccination status of the patient was statistically related to the vaccination status of the HCW (ORa = 4.33, 95% CI: 2.97-8.18, P<0.05). Promoting the vaccination among the population should be dependent on the promotion among HCWs.